The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/geosciences6020019
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Ensembles Tolerant to Synthetic Aperture Radar (SAR) Soil Moisture Retrieval Errors

Abstract: Due to complicated and undefined systematic errors in satellite observation, data assimilation integrating model states with satellite observations is more complicated than field measurements-based data assimilation at a local scale. In the case of Synthetic Aperture Radar (SAR) soil moisture, the systematic errors arising from uncertainties in roughness conditions are significant and unavoidable, but current satellite bias correction methods do not resolve the problems very well. Thus, apart from the bias cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This error range is fundementally different from globally averaged climatology errors estimated over nominal pixels. For backscattering errors, Mattia et al [70] and Lee [61] previously suggested 0.5 to 2 dB.…”
Section: Generation Of Retrieval Ensemblesmentioning
confidence: 99%
See 1 more Smart Citation
“…This error range is fundementally different from globally averaged climatology errors estimated over nominal pixels. For backscattering errors, Mattia et al [70] and Lee [61] previously suggested 0.5 to 2 dB.…”
Section: Generation Of Retrieval Ensemblesmentioning
confidence: 99%
“…We consider it as the ensembles, which are defined as multiple idealizations of "virtual" Figure 3. Nonlinear error propagation of roughness to SAR soil moisture [61]: ASAR backscattering differently retrieved soil moisture products under four roughness conditions indicated in Table. Only scheme #4 is outside of an optimal roughness range.…”
Section: The Concept and Type Of Retrieval Ensemblesmentioning
confidence: 99%
“…The effectiveness of the calibrations was evaluated through the objective functions value and information indicators such as the Akaike information criterion (AIC) and Bayesian information criterion (BIC) [59,60]. The AIC and BIC provide a measure of the relative quality of a model for a given set of data, which considers the number of data, number of model parameters, and the value of the objective function: (12) where N p is the amount of parameters, N inv is the amount of data used in the inverse problem, and O is the objective function value after minimization. The smaller the criterion value, the better the calibration.…”
Section: Strategies Investigated For the Model Calibrationmentioning
confidence: 99%
“…), is soil moisture [9]. Different methods may be used to estimate the soil moisture, which mainly include in situ methods [10], satellite-based data retrieval [11][12][13], and hydrological model based results [14]. The various available methods are generally combined to take advantage of their respective assets [15][16][17], as temporal-spatial scale issues and human-economic means dedicated to monitoring are important limiting factors.…”
Section: Introductionmentioning
confidence: 99%